1997
DOI: 10.1128/mcb.17.1.453
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Mammary Gland Hyperplasia and Carcinomas in Transgenic Mice Expressing Human Cyclin E

Abstract: Deregulated expression of several cell cycle regulatory genes has been demonstrated to be associated with cancer. In particular, a strong correlation has been established between inappropriate cyclin E expression and human breast cancer. To determine the ability of cyclin E to play a causative role in mammary tumorigenesis, regulatory sequences from the ovine ␤-lactoglobulin gene were utilized to specifically target expression of human cyclin E to the mammary glands of pregnant and lactating mice. Lactating ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
165
2
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(173 citation statements)
references
References 42 publications
5
165
2
1
Order By: Relevance
“…This phenomenon is transient, occurring in the epithelia during the lactogenic cycle, initially manifest in the final third of pregnancy and persisting until the litter is weaned at 4 weeks post partum. At this point, the mammary epithelia undergo involution and the hyperplastic epithelia are included in this process (Bortner and Rosenberg, 1997). By standard hematoxylin and eosin staining, hyperplasia in the epithelia of midlactation (2 weeks post partum) mice appeared generally more widespread in T380A transgenic mice than those with the CycE transgene, but no more severe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is transient, occurring in the epithelia during the lactogenic cycle, initially manifest in the final third of pregnancy and persisting until the litter is weaned at 4 weeks post partum. At this point, the mammary epithelia undergo involution and the hyperplastic epithelia are included in this process (Bortner and Rosenberg, 1997). By standard hematoxylin and eosin staining, hyperplasia in the epithelia of midlactation (2 weeks post partum) mice appeared generally more widespread in T380A transgenic mice than those with the CycE transgene, but no more severe.…”
Section: Resultsmentioning
confidence: 99%
“…Chromosomal instability and aneuploidy are thought to be mediators of tumorigenesis. Furthermore, a murine transgenic model expressing cyclin E in the mammary epithelium leads to hyperplasia and mammary tumors (Bortner and Rosenberg, 1997), albeit at a low frequency. In both instances the expression of cyclin E was deregulated with respect to the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, doxorubicin is one of the most valuable anticancer drug in present day clinical use, being an integral part of the treatment of malignancies such as carcinoma of the breast, head and neck, thyroid and soft tissue sarcomas and leukaemias (DeVita et al, 2001). Moreover, on the other hand, increased expression of cyclin E is a common event in a variety of human malignancies (Donnellan and Chetty, 1999;Sandhu and Slingerland, 2000) and is believed to play an important role in cancer development and progression by causing cell growth deregulation and genomic instability (Bortner and Rosenberg, 1997;Spruck et al, 1999). Thus, it has been proposed that cyclin E may become a target for treatment of human cancers (Owa et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The proper timing and amplitude of cyclin E expression are important since their alterations cause deregulation of cell growth (Ohtsubo et al, 1995;Sgambato et al, 1997). Moreover, transgenic mice overexpressing cyclin E develop breast cancers (Bortner and Rosenberg, 1997) and increased levels of cyclin E have been reported in a variety of human malignancies, (Donnellan and Chetty, 1999;Sandhu and Slingerland, 2000).…”
mentioning
confidence: 99%
“…Among human malignancies the strongest correlation was established between breast carcinoma and cyclin E overexpression; here the alterations of cyclin E expression have even been correlated with stage and grade of the disease (Keyomarsi et al, 1994). First experiments with transgenic mice showed that constitutive expression of cyclin E can predispose for the development of mammary tumours after a long latency period (Bortner and Rosenberg, 1997).…”
Section: Introductionmentioning
confidence: 99%